CHARITY IN THE POLITICAL CONTEXT: LEGAL PERMISSIBILITY THROUGH THE APPROACH OF THE AL-UMŪR BIMAQĀṢIDIHĀ PRINCIPLE - Juhari, Andi Rezal; Akmal, Andi Muhammad; Musyahid, Achmad (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This study aims to examine the permissibility of charitable giving (ṣadaqah) in the context of political contests using the al-Umūr bimaqāṣidihā legal maxim approach. The phenomenon of political charity is often equated with money politics, sparking debate among scholars, government authorities, and the public. The discussion explores the concept of ṣadaqah in Islam and the role of intention (niyyah) as the foundation of legal rulings, based on al-Umūr bimaqāṣidihā and its derivative principles. This research employs a qualitative normative method through library research of classical and contemporary Islamic legal sources. The findings indicate that ṣadaqah during political contests is not inherently prohibited, but its legality depends heavily on the giver's intention. If the act is done sincerely for the sake of Allah’s pleasure, it is considered permissible. However, if it is meant to influence voters or gain political support, it is deemed unlawful. In conclusion, government regulations should not impose an absolute ban on political charity, but rather implement strict oversight to ensure that it aligns with sincerity and the principles of fair and honest elections